Strategy for Policy Implementation on HIV/AIDS Prevention in Bali Province - Ida Ayu Putu Sri Widnyani; I Dewa Gede Putra Sedana; I Wayan Mirta; I Nyoman Mangku Suryana (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this article is to investigate the implementation of HIV/AIDS prevention policies at the Bali Provincial AIDS Commission. Despite the fact that the Bali Province has published an HIV/AIDS prevention strategy, there are still cases. The research method employed is a qualitative descriptive method. The data is then collected through interviews and documentation. According to the research findings, the Bali Provincial AIDS Commission's implementation of the HIV/AIDS Control Policy has not been carried out optimally. The constraints that become problems are the standard and policy objectives, resources, characteristics of implementing organizations, dispositions (attitudes) of implementers, and communication between implementing organizations and the social, political, and economic environment. From the common factors and policy objectives, there is no Regional Action Plan Strategy, and KPA Strategic Plan, human and financial resources are still lacking, so they need to be maximized; from the characteristics of the implementing organization, not all stakeholders carry out and carry out their roles in HIV/AIDS prevention efforts, public attitudes are still less sensitive against HIV/AIDS prevention efforts, communication between stakeholders and the community has not been in the same direction and line with the environmental conditions of the community, which are not yet conducive, there is still a stigma against people living with HIV/AIDS (PLWHA).